CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel